Analisis Perencanaan Produksi Mebel Menggunakan Perangkat Lunak Berbasis Fuzzy Linear Programming serta Pengujian Akurasi Hasil Menggunakan Data Training dan Data Testing - Mardiansyah, Mardiansyah; Rivai, Abu Khalid; Kurnia, Dadang (Jurnal Informatika Universitas Pamulang, 2021)
For the management of raw material supply problems and optimization of the production process, appropriate methods are needed, fuzzy linear programming algorithm is the right model to provide recommendations related to production forecasting problems. The results of the prediction of ideal production potential provide recommendations for the optimal profit that will be obtained if selling 10 kitchen set products, 10 work tables and 10 wardrobes, with this sale the company will get an income of Rp. 154,500,000. Forecasting results have been tested using training data and testing data, the recommendations given by the system have an accuracy of 97.8%.